Chapter Wandering around the edges of the arts and humanities - Hearn, Jeff (Amsterdam University Press, 2023)
Writing sometimes involves wandering. This writing seeks to say and show what it is to write wandering around the edges of the arts and humanities. It also concerns why some writing is difficult, and thence writing on some of those difficulties. These problematics are wandered around, by several rounds - some images invoked by edge-wandering; registering particular significant individuals; how particular places persist in understandings of wandering; disciplines and methodologies, including reflecting on spatiality and locationality; interdisciplinarity and academia; transnational wanderings across writing genres; and relations of art, humanities, science and politics, understood as personal, work, political and theoretical.